Woody plant diversity in sacred forests and fallows in Chiang Mai, Thailand - Auemporn Junsongduang (2018)
© 2014, Chiang Mai University. All rights reserved. All woody plant and seedling diversity was compared in a Karen and a Lawa hill-tribe village in northern Thailand in four different habitats: sacred forests and fallow fields of three ages derived from rotational shifting cultivation (young fallows, 1–2 years old; medium-age fallow, 3-4 years old; old fallow, 5-6 years old). All woody plant species were identified and counted in three transects (20 x 40 m). Seedlings were inventoried in 12 circular (5 m diam.) plots. The highest species richness of all woody species and seedlings were found in the sacred forests in both villages. The highest values of the Shannon-Wiener index for both trees and seedlings were in the sacred forest of the Karen village. There were significant differences in species richness between the four studied habitats surrounding both villages (p < 0.05). All woody plant and seedlings species compositions in the sacred forests of both villages were distinct from all the fallow plots as revealed by cluster analysis. Pearson’s correlation test showed that only the Simpson diversity index was significantly and positively related to distances from the fallows to the sacred forest. The percentages of plants originating from sprouts were highest in the young fallow and decreased when the fallows aged in both villages, and vice versa for plants originated from seedlings. Furthermore, the sacred forest of both villages harbored endemic and threatened species in Thailand.